Correlation between basal metabolic rate, visceral fat and insulin resistance among type 2 diabetes mellitus with peripheral neuropathy. Issue 1 (January 2019) - Sampath Kumar, A.; Arun Maiya, G.; Shastry, B.A.; Vaishali, K.; Maiya, Shubha; Umakanth, Shashikiran
Abstract: Background: Basal Metabolic Rate (BMR) means the amount of energy utilized by body in physical and psychological resting rate, after a night sleep, awake without any previous physical activity post meal (10 h after last meal) & neutral environment. In people with type 2 diabetes mellitus (T2DM) there is an increase in BMR which is said to be associated with the level of glycaemic control. So, the objective of the study was to find out the correlation between BMR, Insulin resistance and Visceral fat in T2DM with peripheral neuropathy. Materials & methods: A total of 50 participants with T2DM with peripheral neuropathy were included. Age group of 30–75 years were selected for the study. Participants with a known history of neurological disease, locomotor disability, and pregnancy were excluded from the study. Demographic details of the participants like duration of diabetes mellitus, age, Fasting Blood Glucose, Fasting Insulin, HOMA-IR, Glycated Haemoglobin (HBA1c), Neuropathy and Blood pressure values were noted. We measured Basal Metabolic Rate (BMR) by using Mifflin-St Jeor predictive equation in T2DM with peripheral neuropathy. Results: The mean age of the participants is 60.16 ± 10.62. The mean duration of T2DM 13.44 ± 11.92. In the present study we found a statistical significant correlation between BMR and HOMA IR (r = 0.913*; p = 0.000), BMR & Fasting blood sugar (FBS) (r = 0.281*; p = 0.048), BMR and Visceral fat (VF) (r = 0.332*; p = 0.018). Conclusion: Basal metabolic rate is correlated to Homa-IR, visceral fat, fasting blood sugar and musculoskeletal mass among T2DM with peripheral neuropathy. Highlights: Measurement of BMR is in people with T2DM there is an increase in BMR which is said to with the of glycaemic control. BMR accounts for approximately 60% of total daily energy expenditure, making it the most parameter for determining appropriate energy intake. To the best of our knowledge, this is the first study conducted in India which reported about BMR with IR & VF among T2DM with peripheral neuropathy.